Safety as a social value: Revisiting a participatory case study in Scotland - Roberts, H.; Smith, Susan; Campbell, B.; Rice, C. (2011)
This chapter revisits research carried out in the early 1990s in Scotland on child accidents-a key public health problem in rich and poor nations alike, and one where there are stark differences between better off and worse off children. The research (Roberts, Smith, & Bryce, 1995) was forged through a close collaboration with the residents of Corkerhill, a former railway village in Glasgow, Scotland. © 2011 Springer Science+Business Media, LLC.